Prevalence of hypokalemia in COVID-19 and its association with clinical and common laboratory parameters (Journal of Dhaka Medical College, 2021)
Importance: Hypokalemia is a neglected common manifestation in COVID-19 patients admitted in hospital though it has serious consequences. Coronavirus may cause hypokalemia through disruptions of rennin-angiotensin system, gastrointestinal loss or other unknown mechanisms.Objective: To investigate the prevalence of hypokalemia among patients with moderate to severe COVID-19 and its association with other clinical and laboratory parameters.Design, Setting, and Participants: This was cross sectional observational study conducted at Dhaka medical College Hospital of Bangladesh from June, 2020, to August 2020. Participants were included who were positive for rt-PCR for COVID-19 according to the national guideline. The patients were classified as having severe hypokalemia (plasma potassium 3.5 mmol/L).Results: Prevalence of hypokalemia among patients with COVID-19 was 20.2%, severe hypokalemia (2 patients [1.5%]) and hypokalemia (25 patients [18.7%]). One thirty four (134) patients with positive COVID-19 were included. The mean [SD] age of these 134 patients according to different potassium levels appear to be : 68 [2.83] years for severe hypokalemia , 51.93[11.68] years for hypokalemia and 50.73[14.7] years for normokalemia. Among them, 46 patients were females [34.32%]) and rest were males [65.68%]. Within the total sum of 134 patients, 107 were identified having normokalemia, [79.9%]. 25 patients [18. 7%] had hypokalemia and only two patients [1.5%] were found having normokalemia. Among 134 patients, three commonest symptoms were fever (132 patients [98.5%]), dry cough (123 patients (91.79%) and shortness of breath (122 patients [91.04%]), followed by less common symptoms like fatigue (89 patients [66.410%]), sore throat (60 patients [44.77%]), and diarrhea (44 patients, [32.83%]). Shortness of breath was associated with grades of hypokalemia (P=0.022). Only 26 patients (19.4%) manifested having vomiting/Nausea. The predominant comorbidities found among these 134 participants were Hypertension (68 patients [64.2%]), Diabetes (54 patients [52.9%]), Ischemic heart disease (37 patients [38.1%]) and Asthma (27 patients [31.0%]). The prevalence of comorbidities was not associated with Hypokalemia.Conclusions Prevalence of hypokalemia among patients with COVID-19 is high (20.2%) and appropriate treatment is highly required.J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 131-137